Novel Pharmacology Following Heteromerization of the Angiotensin II Type 2 Receptor and the Bradykinin Type 2 Receptor - Johnstone, Elizabeth K. M.; Ayoub, Mohammed Akli; Hertzman, Rebecca J.; See, Heng B.; Abhayawardana, Rekhati S.; Seeber, Ruth M.; Pfleger, Kevin D. G. (Frontiers in Endocrinology, 2022)
The angiotensin type 2 (AT2) receptor and the bradykinin type 2 (B2) receptor are G protein-coupled receptors (GPCRs) that have major roles in the cardiovascular system. The two receptors are known to functionally interact at various levels, and there is some evidence that the observed crosstalk may occur as a result of heteromerization. We investigated evidence for heteromerization of the AT2 receptor and the B2 receptor in HEK293FT cells using various bioluminescence resonance energy transfer (BRET)-proximity based assays, including the Receptor Heteromer Investigation Technology (Receptor-HIT) and the NanoBRET ligand-binding assay. The Receptor-HIT assay showed that Gq, GRK2 and β-arrestin2 recruitment proximal to AT2 receptors only occurred upon B2 receptor coexpression and activation, all of which is indicative of AT2-B2 receptor heteromerization. Additionally, we also observed specific coupling of the B2 receptor with the Gz protein, and this was found only in cells coexpressing both receptors and stimulated with bradykinin. The recruitment of Gz, Gq, GRK2 and β-arrestin2 was inhibited by B2 receptor but not AT2 receptor antagonism, indicating the importance of B2 receptor activation within AT2-B2 heteromers. The close proximity between the AT2 receptor and B2 receptor at the cell surface was also demonstrated with the NanoBRET ligand-binding assay. Together, our data demonstrate functional interaction between the AT2 receptor and B2 receptor in HEK293FT cells, resulting in novel pharmacology for both receptors with regard to Gq/GRK2/β-arrestin2 recruitment (AT2 receptor) and Gz protein coupling (B2 receptor). Our study has revealed a new mechanism for the enigmatic and poorly characterized AT2 receptor to be functionally active within cells, further illustrating the role of heteromerization in the diversity of GPCR pharmacology and signaling.